Measuring Integrated Market and Credit Risks in Bank Portfolios : An Application to a Set of Hypothetical Banks Operation in South Africa - Papapanagiotou, Panagiotis (IMF Working Papers; Working Paper ;, 2000)
The banking crises of the 1990s emphasize the need to model the connections between volatility and the potential losses faced by financial institutions due to correlated market and credit risks. We present a simulation model that explicitly links changes in the financial environment and the distribution of future bank capital ratios. This forward-looking quantitative risk assessment methodology allows banks and regulators to identify risks before they materialize and make appropriate adjustments to banks' portfolios. This model was applied to the study of the risk profile of the largest South African banks in the context of the Financial System Stability Assessment (FSSA) (1999).